INTERACTIVE ELECTRONIC MODULE INTEGRATED WITH AUGMENTED REALITY CONTEXT OF LOCAL WISDOM OF JAMBI CULTURE - Muslimahayati Muslimahayati; Fiqi Nurmanda Sari (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
There are many studies discussing the development of interactive electronic modules, but only a few integrate them using Augmented Reality and local culture. This study aims to develop a valid and practical interactive E-Module using Augmented Reality technology with the context of Jambi's local cultural wisdom as an alternative interesting teaching material to visualize a concept in increasing understanding related to the structure of an object that is relevant to everyday life. The research was developed with 4D stages (Define, Design, Develop, and Disseminate). Data collection was carried out using expert validation sheets, practicality questionnaire sheets and documentation. The results of the study indicate that the developed e-module is valid and practical. The results of media and material validation at the expert validation stage showed results of 96.86% and 93.75% that the e-module has been valid and very well developed. Practicality is seen at the small group stage (3 high-ability students, 3 medium-ability students and 3 low-ability students) which gave results of 85.415% so that the e-module is practical and categorized as very good. Furthermore, the field test (17 students) provided a descriptively positive response to the developed electronic module. This research also impacts the process of transforming culture into a learning medium, providing solutions for cultural preservation in the digital age, and fostering positive energy between education, culture, and the use of technology in learning.